Cross-seam Hybrid MTDC System for Integration and Delivery of Large-scale Renewable Energy - Kaiqi Sun (IEEE, 2021)
To better utilize the diversity of renewable energies in the U.S., this paper proposes a cross-seam hybrid multi-ter-minal high-voltage direct current (MTDC) system for the integration of different types of renewable energies in the U. S. Based on a developed station-hybrid converter design, the proposed hybrid MTDC system further investigates the connection methods of renewable energies and develops novel flexible power flow control strategies for realizing uninterrupted integration of renewable energies. In addition, the frequency response control of the hybrid MTDC system is proposed by utilizing the coordination between the converters in the hybrid MTDC system. The feasibility of the hybrid MTDC system and the performance of its corresponding control strategies are conducted in the PSCAD/EMTDC simulation. The simulation results indicate that the proposed hybrid MTDC system could realize the uninterrupted integration of renewable energies and flexible power transmission to both coasts of U.S.